1997
DOI: 10.1101/gad.11.4.504
|View full text |Cite
|
Sign up to set email alerts
|

Cdc2 tyrosine phosphorylation is required for the DNA damage checkpoint in fission yeast.

Abstract: A common cellular response to DNA damage is cell cycle arrest. This checkpoint control has been the subject of intensive genetic investigation, but the biochemical mechanism that prevents mitosis following DNA damage is unknown. In Schizosaccbaromyces potnbe, as well as vertebrates, the timing of mitosis under normal circumstances is determined by the balance of kinases and phosphatases that regulate inhibitory phosphorylation of Cdc2. In S. pombe, the phosphorylation occurs on tyrosine-15. This method of mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
215
1
5

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(225 citation statements)
references
References 43 publications
(53 reference statements)
4
215
1
5
Order By: Relevance
“…In S. pombe several mutants have been described that are unable to arrest the cell cycle in response to DNA damage at the G2 checkpoint (Weinert and Hartwell, 1990;AlKhodairy et al, 1994;Ford et al, 1994). One of these genes, chk1, encodes a protein kinase that appears to function downstream of all other checkpoint genes to elicit a cell cycle arrest via cdc25 and wee1 to maintain tyrosine phosphorylation of p34 cdc2 (O'Connell et al, 1997;Rhind et al, 1997;Furnari et al, 1997;Sanchez et al, 1997). Irradiation of cells leads to phosphorylation of chk1 itself, and this response requires all of the upstream checkpoint components, including rad3 (Walworth and Bernards, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In S. pombe several mutants have been described that are unable to arrest the cell cycle in response to DNA damage at the G2 checkpoint (Weinert and Hartwell, 1990;AlKhodairy et al, 1994;Ford et al, 1994). One of these genes, chk1, encodes a protein kinase that appears to function downstream of all other checkpoint genes to elicit a cell cycle arrest via cdc25 and wee1 to maintain tyrosine phosphorylation of p34 cdc2 (O'Connell et al, 1997;Rhind et al, 1997;Furnari et al, 1997;Sanchez et al, 1997). Irradiation of cells leads to phosphorylation of chk1 itself, and this response requires all of the upstream checkpoint components, including rad3 (Walworth and Bernards, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism(s) for G2 checkpoint activation in response to DNA damage remains unclear but recent data with S. pombe support a model where chk1 protein kinase maintains p34 cdc2 in its tyrosine phosphorylated, inactive state for the duration of the checkpoint arrest (O'Connell et al, 1997;Rhind et al, 1997). Overexpression of chk1 in wild type S. pombe led to cellular elongation and a failure to enter mitosis (Al-Khodairy et al, 1994;Ford et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, details of the G2 DNA damage checkpoint (G2DDC) pathway that impinges on the cell cycle have been elucidated (Nurse, 1997;Weinert, 1997). It is now being suggested that the G2DDC pathway perturbs the cell cycle via Cdc25 (Furnari et al, 1996;Rhind et al, 1997). There are, however, reports that also link the damage pathway with Wee1 (O'Connell et al, 1997), and there is still some uncertainty as to which of Cdc25 or Wee1 is the target of the damage checkpoint pathway (Osmani and Ye, 1997).…”
Section: Coupling Of the Pd Cycles Involving Cdc25 Wee1 And Mpfmentioning
confidence: 99%
“…DNA lesions caused by different damaging agents may activate different cell cycle checkpoints and inhibit different Cdk activities (Attardi et al, 2004;Buscemi et al, 2004;Sancar et al, 2004). Previous studies have established that DNA damageinduced Cdk inhibition can be caused by downregulation of cyclins (Muschel et al, 1991(Muschel et al, , 1992Datta et al, 1992;Poon et al, 1996;Agami and Bernards, 2000;Miyakawa and Matsushime, 2001), inhibition of complex formation between a Cdk and its cyclin partner (Zhan et al, 1999), induction of inhibitory tyrosine phosphorylation of Cdks (Terada et al, 1995;Jin et al, 1996;Poon et al, 1996;Blasina et al, 1997;Rhind et al, 1997;Ye et al, 1997), inhibition of activating phosphorylation of Cdks (Smits et al, 2000), or induction of the Cdk inhibitor p21 by p53 (Dulic et al, 1994;el-Deiry et al, 1994).…”
Section: Introductionmentioning
confidence: 99%